Study of Comparison of Dexmedetomidine Added to Levobupivacaine versus Alone Levobupivacaine in Supraclavicular Brachial Plexus Blockade - Brahmbhatt, Nimisha; Mehta, Swati (Academia Anesthesiologica International, 2020)
Background: The aim is the current research is the comparison of Dexmedetomidine added to Levobupivacaine versus alone Levobupivacaine in supraclavicular brachial plexus blockade. Subjects and Methods : The current research was performed in the Department of Aneshtesia, Gov- ernment Medical College and SSG Hospital, Vadodara, from October 2014tooctober to 2015. Subjects were separated into 2 groups: Group LD: receives Inj. Levobupivacaine 0.5 %(35ml)+inj.Dexmedetomidine (0.5 l)+Inj.NS(0.5ml)=total 36 ml. Group L: receives Inj.Levobupivacaine0.5 %( 35ml) + inj. Normal saline(1ml) = 36 ml. Pulse rate, Blood pressure, Respiratory rate and Oxygen saturation (SpO2), Ramsay sedation score were monitored before giving the block, immediately after giving the block, each 5 minutes till fifteen minutes, every fifteen minutes thereafter for one hour and each thirty minutes afterward until the conclusion of surgery. Results: Total duration of sensory block was significantly extended in group LD as a contrast to group L. Total duration of motor block was significantly longer in group LD as a contrast to group L. Patients receiving Dexmedetomidine had long-lasting postoperative analgesia as compared to the control group. Thus, the total duration of analgesia was considerably extended in group LD patients as a contrast to group L patients and the dissimilarity was statistically highly significant. Conclusion: Dexmedetomidine can be utilized as a secure and useful aid to local anesthetics in supraclavicular brachial plexus block to give outstanding perioperative analgesia with negligible consequences.